PEMANFAATAN JURNAL ONLINE PERPUSTAKAAN BPTP YOGYAKARTA - Dwi Titaningsih; Suharno Suharno (Jurnal Pustaka Ilmiah, 2016)
The online journal is one of the sources of information from various sources of information availability, available good from the hearts and abroad to get literature review. It is influenced by the development of technology and information wichis increasingly advanced so that information can be obtained easily.Along with advances in information technology (ICT), efforts in obtaining and providing information is not limited to the distance, space, and time. The use of the online journal by researchers and extension workers are rarely used. The use of the online journal by researchersand extension workers are rarely used. Effort to examine the use of online journals was conducted to determine show far the use of the online journal by researchers, extension workers, and other library user in IAIT Yogyakarta. The studies was conducted in September 2015 and arranged in randomized design with 30 respondents. The result of this studies showed that (1) frequency of using journal online are more dominant in one to two times a week wich is done by 22 library user (73,34%), (2) the length of time utilization for accessing online journals most are one to two hours wich is done by 13 library user (43,34%), (3) the level of ability of library user wich using Boolean operator AND, OR, NOT evidently 11 library user does not understand (36,67%), (4) the action to download from the search result conducted by is library user (50%), (5) The access point information in the most preferred search by keyword is done by 21 library user (70%), (6) the purpose of utilizing the online journal access research were 12 library user (40%), (7) completeness of information required by library user perceived by 23 library user (76,66%), (8) accesing online journal wich are mostly done at the work space is as much as 20 library user (66,67%), (9) the domestic online journals are more affractive was choosen by 17 library user (56,66%).